Accounting System Recording and Financial Reporting at Kedai Kopi Ameng - Iskandar Itan; Natasya Artamevia (Universitas Internasional Batam, 2023)
To facilitate the running of a business, it is necessary to record accounting, accounting records in the form of recording transactions that can affect financial conditions. Good accounting records can be used as a basis for decision making. This research chooses MSMEs engaged in services and semi manufacturing under the name Kedai Kopi Ameng. From 1980 to present, MSMEs do not yet have an accurate and efficient accounting recording system. Recording of income is still in manual form by using records in the form of books and does not yet have accurate records for expenses for business operational costs. So that business owners find it difficult to make decisions and know the advantages or disadvantages of the business. The scope of this research is the creation of a computerized accounting recording system using Ms. Access that generates financial reports as output. This is done so that MSME owners can use the system well, get a positive influence, and can facilitate accounting recording activities. As a result, it is easier for owners to get information more quickly, precisely, and can be used to help make financial decisions for owners.